Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/os.13670
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Percutaneous Kyphoplasty Using a Novel Guide Device for Thoracolumbar Osteoporotic Vertebral Fracture

Abstract: Objectives: Unilateral percutaneous kyphoplasty (UPKP) has been effective in reducing the operative time, cement volume, and cement leakage (CL) rate compared with bilateral kyphoplasty. However, no device can help to determine the trajectory during operation, especially the inner inclination angle. To assess the safety and efficacy of a novel guide device (GD) for UPKP in the treatment of thoracolumbar osteoporotic vertebral fractures (TLOVFs).Methods: From January 2019 to May 2021, 31 patients diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We have given much attention to the preoperative planning [14,15] and 3D printing technologies [16][17][18][19][20] used in percutaneous vertebroplasty (PVP)/PKP, and previous studies have shown that PVP with preoperative puncture design is not only reasonably safe and effective for OVCFs but also involves less radiation, shorter operation times and fewer complications than traditional PVP [14,15]. Our research has indicated that unilateral puncture using a novel 3D-printed guide device is a safe and effective technique for OVCFs and is associated with fewer intraoperative fluoroscopy exposures and shorter operation times [21]. During PKP, the conventional methods used for Jamshidi needle placement and guidewire advancement into the pedicle require numerous radiographic images.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…We have given much attention to the preoperative planning [14,15] and 3D printing technologies [16][17][18][19][20] used in percutaneous vertebroplasty (PVP)/PKP, and previous studies have shown that PVP with preoperative puncture design is not only reasonably safe and effective for OVCFs but also involves less radiation, shorter operation times and fewer complications than traditional PVP [14,15]. Our research has indicated that unilateral puncture using a novel 3D-printed guide device is a safe and effective technique for OVCFs and is associated with fewer intraoperative fluoroscopy exposures and shorter operation times [21]. During PKP, the conventional methods used for Jamshidi needle placement and guidewire advancement into the pedicle require numerous radiographic images.…”
Section: Introductionmentioning
confidence: 83%
“…In previous studies, preoperatively designed PVP involved less radiation, a shorter operation and fewer complications than traditional PVP [14,15]. Our previous research has also indicated that unilateral PKP using a novel 3D-printed guide device is a safe and effective technique for OVCFs [21]. The 3D-printed guide devices, including an intradermal locator and an angle-measuring device, were used to accurately determine the entry point and angle of trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations